Interstitial Occupancy by Extrinsic Alkali Cations in Perovskites and Its Impact on Ion Migration. Issue 26 (7th May 2018) - Cao, Jie; Tao, Shu Xia; Bobbert, Peter A.; Wong, Ching‐Ping; Zhao, Ni
Abstract: Recent success in achieving highly stable Rb‐containing organolead halide perovskites has indicated the possibility of incorporating small monovalent cations, which cannot fit in the lead‐halide cage with an appropriate tolerance factor, into the perovskite lattice while maintaining a pure stable "black" phase. In this study, through a combined experimental and theoretical investigation by density functional theory (DFT) calculations on the incorporation of extrinsic alkali cations (Rb +, K +, Na +, and Li + ) in perovskite materials, the size‐dependent interstitial occupancy of these cations in the perovskite lattice is unambiguously revealed. Interestingly, DFT calculations predict the increased ion migration barriers in the lattice after the interstitial occupancy. To verify this prediction, ion migration behavior is characterized through hysteresis analysis of solar cells, electrical poling, temperature‐dependent conductivity, and time‐dependent photoluminescence measurements. The results collectively point to the suppression of ion migration after lattice interstitial occupancy by extrinsic alkali cations. The findings of this study provide new material design principles to manipulate the structural and ionic properties of multication perovskite materials. Abstract : Interstitial occupancy in a perovskite lattice by small alkali cations is proposed and verified through a combined experimental and theoretical investigation. Density functional theory calculations and ion‐migration characterization further reveal increased ion‐migration barriers due to the presence of interstitial alkali cations. These findings provide new material design principles to manipulate the structural and ionic properties of the multication perovskite materials.